INTEGRASI NILAI-NILAI ANTI KORUPSI PADA MATA PELAJARAN KIMIA MELALUI MEDIA GAME ULAR TANGGA - Erlawana Erlawana (UIN AR-RANIRY, 2017)
This research moved from the unfolding phenomenon of corruption cases in Indonesia which is on evidence of unsuccesfull education world. One of the efforts is to arouse creativity, confidence, and passion to always be productive, responsibility so as not provoke by committing cheating and instant acts. Here we need innovative learning models that can give rise to awareness of goodness. The purpose of this research is to find out the integration of anti corruption values of chemical subject in SMAN 13 Banda Aceh and implementing anti corruption value to the student since early stage through snake and ladders game. The subject of this research is students grade X-MIA first semester academic year 2014/2015, the total amount is 25 students wich consist of 14 male and 11 female. This research was conducted in two meetings. The first meeting is divided into two stages: first, 1 JP to implement anti values trough video and the next, 2 JP with chemical bonding material. Whereas in the second meeting, the first 2 JP for snakes and ladders and the following 1 JP is for evaluation. Based and the result of attitude assessment of there is only one student whose grades rated C, for psychomotor assessment, all students succeed while in cognitive assessment there are four students who have not reached the KKM 2.66 (B-) with students total presentage abaout chemical bonding material reached 84%. Through snake and ladders game it can implement anti corruption values to students since early stage. It can be seen that the learning process each student have shown core (honesty, discipline, responsibility), work ethic (hard work, shumble, and indipendent) and attitudes (fair, brave and caring).